Adsorption of Basic Dyes onto Natural Clay - S. Guiza; M. Bagane; A.H. Al-Soudani; H. Ben Amore (Adsorption Science & Technology)
The adsorption ability of natural clay towards the removal of basic dyes from aqueous textile solutions was investigated. The equilibrium isotherms were measured and analyzed using the Langmuir model and the experimental results compared with the theoretical data. The adsorbent exhibited considerable adsorption capacities of 567, 526, 427 and 300 mg/g towards Neutral Red, Methyl Violet, Methyl Green and Methylene Blue, respectively. Thus, the clay may be used as a cost-effective industrial adsorbent for the removal of basic dyes from industrial effluents.